2020
DOI: 10.1101/2020.07.23.217844
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mild membrane depolarization in neurons induces immediate early gene transcription and acutely subdues responses to successive stimulus

Abstract: The transcriptional profile of immediate early genes (IEGs) is indicative of the duration of neuronal activity, but it is unknown whether it affected by the strength of depolarization. Also unknown is whether an activity history of graded potential changes influences further neuronal activity. In this work with dissociated rat cortical neurons, we found mild depolarization – mediated by elevated extracellular KCl – not only induces a wide array of rapid IEGs, but also transiently depresses transcriptional and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…This does not bring the resting membrane potential to zero, but it is sufficient to induce robust gene expression. We have found that lower concentrations of KCl (mild depolarization) are also potent inducer of neuronal IEG transcription ( Rienecker et al., 2020 ). Treatment times also vary widely, from 10 seconds to 48 hours.…”
Section: Effects Of Duration and Doses Of Elevated External Potassiummentioning
confidence: 99%
See 1 more Smart Citation
“…This does not bring the resting membrane potential to zero, but it is sufficient to induce robust gene expression. We have found that lower concentrations of KCl (mild depolarization) are also potent inducer of neuronal IEG transcription ( Rienecker et al., 2020 ). Treatment times also vary widely, from 10 seconds to 48 hours.…”
Section: Effects Of Duration and Doses Of Elevated External Potassiummentioning
confidence: 99%
“…However, to our knowledge, there has not been a methodical investigation into whether varied concentrations and treatment times interact to produce different gene expression profiles. We might expect variation, as different concentrations of intracellular Ca 2+ and modes of Ca 2+ entry differentially induce different signaling pathways, resulting in distinct transcriptional profiles ( Rajadhyaksha and Kosofsky, 2005 ; Tyssowski et al., 2018 ; Rienecker et al., 2020 ). In Table 1 , we have compiled and sorted selected papers by KCl concentration and time of treatment.…”
Section: Effects Of Duration and Doses Of Elevated External Potassiummentioning
confidence: 99%